(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The new coronavirus control efforts have resulted in a change in the educational environment,with online courses replacing in-person instruction. There has been a shift toward offering coursesonline in K-12 and higher education. It may be too soon to tell how students and teachers will adjust toonline learning as they become aware of its limitations and reorient themselves to meet them, but wehave tried to document the viewpoint and preparation of teachers and students as a critical component.The majority of respondents to this study had a positive view of online learning following HurricaneCorona. Since the internet format allowed for more flexibility and convenience, it was deemedsuccessful. Students preferred materials that were well-organized and included filmed movies that weremade available on university websites. Students also said that they would recall more material if eachcourse concluded with an exam and a project. However, the majority of students also expressed concernthat online classes could be more challenging than face-to-face ones owing to technological constraints,slower feedback, and professors who aren’t proficient in effectively using ICTs. In order to create anonline course that is effective for its intended audience, it is crucial to consider the aforementionedfactors.When the smoke from the COVID-19 epidemic clears, more schools may turn to online learningas a supplementary method of education. As a result, the results of this study will be useful forindividuals who are thinking about incorporating online components into more conventional forms ofhigher education.